1997
DOI: 10.1111/j.1365-2958.1997.mmi494.x
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of novel choline‐binding proteins to adherence, colonization and immunogenicity of Streptococcus pneumoniae

Abstract: SummaryThe surface of Streptococcus pneumoniae is decorated with a family of choline-binding proteins (CBPs) that are non-covalently bound to the phosphorylcholine of the teichoic acid. Two examples (PspA, a protective antigen, and LytA, the major autolysin) have been well characterized. We identified additional CPBs and characterized a new CBP, CbpA, as an adhesin and a determinant of virulence. Using choline immobilized on a solid matrix, a mixture of proteins from a pspA-deficient strain of pneumococcus was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
469
0
6

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 438 publications
(494 citation statements)
references
References 42 publications
19
469
0
6
Order By: Relevance
“…Subsequent invasion of human endothelial cells is promoted by cytokine activation which increases the amount of surface-expressed platelet-activating factor (PAF) re- ceptor that in turn binds to the phosphorylcholine component of the cell wall [28]. An adhesin CbpA promotes increased attachment to activated human cells [29]. Recent studies showed that pneumococci could bind to reconstituted basement membrane as well as to a purified laminin component [4].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent invasion of human endothelial cells is promoted by cytokine activation which increases the amount of surface-expressed platelet-activating factor (PAF) re- ceptor that in turn binds to the phosphorylcholine component of the cell wall [28]. An adhesin CbpA promotes increased attachment to activated human cells [29]. Recent studies showed that pneumococci could bind to reconstituted basement membrane as well as to a purified laminin component [4].…”
Section: Discussionmentioning
confidence: 99%
“…The ectodomain of pIgR is also known as the secretory component (SC), and independent reports have indicated that the human specificity of the PspC-SC interaction is determined by amino acid differences in ectodomains D3 and D4 of the SC (Elm et al, 2004;Lu et al, 2003). Despite such human specificity, loss of function in PspC has been shown to reduce colonization of infant rats (Rosenow et al, 1997) and pIgR knockout mice (Zhang et al, 2000). The hexameric SC-binding site in PspC is located in N-terminal repeated domains (Hammerschmidt et al, 2000), recently designated R1 and R2.…”
Section: Biological Activities Of Unusually Cell-wallanchored Cholinementioning
confidence: 99%
“…Three proteins possibly involved in specific interaction between L. reuteri and its host were identified: Lre0019 with similarities to the S. pneumoniae PspC; Lre0018 with similarities to the Lactobacillus johnsonii Apf1; and the previously described CnBP (Roos et al, 1996). The cell surface adhesin PspC is involved in colonization of mucosal surfaces in the nasopharynx (Balachandran et al, 2002;Rosenow et al, 1997). The protein interferes with the complement pathway by binding to the third component, C3 (Cheng et al, 2000), and to factor H (Dave et al, 2001).…”
Section: Prediction Of the Protein Functionsmentioning
confidence: 99%